Investigation of antioxidative constituents from the stem of entada spiralis / Norshazleen Mohd Azenan - Mohd Azenan, Norshazleen (Faculty of Applied Sciences, 2017)
This study is about the determination of antioxidant activity in the stem of E. spiralis. Phytochemical screening test was performed by using the methanol extraction. Then, the methanol extract was proceed to determine the functional group using FTIR. Thin Layer Chromatographic (TLC) Analysis was developed to identify the compound that presence in the stem of E. spiralis. Each TLC was sprayed by using spraying reagent to identify compound that contains in each extract. After the extraction of methanol, dichloromethane, and petroleum ether was done, the best solvent system was used to developed TLC analysis. The best solvent system for MeOH extraction is 27:3 (HEX:EA), DCM extraction is 29.4:0.6 (DCM:MeOH), and PE extraction is 24:6 (Chloroform :Acetone). Then, serial dilution was conducted to investigate the antioxidative assay in the stem of E. spiralis and also identify IC50. Methanol extract has the highest antioxidant activity. Isolation of antioxidative compound from PE extract from different Rf then proceed with GC-MS analysis. Oxiraneoctanoic acid, 3-octyl-, cis, 9,12 Octadecadienoic acid, Hexadecanoic acid, 1-(hydroxymethyl)-1,2-ethanediyl ester, Butylaldehyde, 4-benzyloxy-4-[2,2,-dimethyl-4-dioxolanyl], Butylaldehyde, 4-benzyloxy-4-[2,2,-dimethyl-4-dioxolanyl], Hexadecanoic acid, methyl ester, IH-Indene, I-methylene, Benzene, 1,2,4,5-tetramethyl, and trans-Verbenyl isovalerate have been isolated and identified by GC-MS.